A comprehensive review on chlorpyrifos toxicity with special reference to endocrine disruption: Evidence of mechanisms, exposures and mitigation strategies - Ubaid ur Rahman, Hafiz; Asghar, Waqas; Nazir, Wahab; Sandhu, Mansur Abdullah; Ahmed, Anwaar; Khalid, Nauman (The Science of the total environment, 2021)
Chlorpyrifos (CPF) is a broad-spectrum chlorinated organophosphate (OP) pesticide used for the control of a variety of insects and pathogens in crops, fruits, vegetables, as well as households, and various other locations. The toxicity of CPF has been associated with neurological dysfunctions, endocrine disruption, and cardiovascular diseases (CVDs). It can also induce developmental and behavioral anomalies, hematological malignancies, genotoxicity, histopathological aberrations, immunotoxicity, and oxidative stress as evidenced by animal modeling. Moreover, eye irritation and dermatological defects are also reported due to CPF toxicity. The mechanism of action of CPF involves blocking the active sites of the enzyme, acetylcholinesterase (AChE), thereby producing adverse nervous system effects. Although CPF has low persistence in the body, its active metabolites, 3,5,6-trichloro-2-pyridinol (TCP), and chlorpyrifos-oxon (CPO) are comparatively more persistent, albeit equally toxic, and thus produce serious health complications. The present review has been compiled taking into account the work related to CPF toxicity and provides a brief compilation of CPF-induced defects in animals and humans, emphasizing the abnormalities leading to endocrine disruption, neurotoxicity, reproductive carcinogenesis, and disruptive mammary gland functionality. Moreover, the clinical signs and symptoms associated with the CPF exposure along with the possible pharmacological treatment are reported in this treatise. Additionally, the effect of food processing methods in reducing CPF residues from different agricultural commodities and dietary interventions to curtail the toxicity of CPF has also been discussed. [Display omitted] •Chlorpyrifos (CPF) is an extensively used insecticide for fruits and vegetables.•CPF contributes towards the air, water, and land pollution.•Dietary sources are the foremost cause of non-occupational CPF exposure in humans.•A number of CPF intoxication incidents have been reported around the world.•CPF and its environmental degradation products are associated with endocrine disruption.